Use of local herbal galactagogues by Nigerien women to enhance breast milk production - Lawaly, Maman Manzo; Ikhiri, Khalid (Recent Research in Science and Technology, 2025)
Breastfeeding is recognized as an effective way to save children’s lives. Nigerien breastfeeding mothers with insufficient milk production traditionally use medicinal plants to enhance milk yield, despite of absence of scientific reports confirming the evidence-based safety and efficacy of these practices. The aim of this study is to review the ethnomedicinal knowledge about the use of medicinal plants to promote lactation in breastfeeding mothers by Nigerien peoples, and to assess their evidence-based toxicological and chemical studies reported across the world. Relevant data about the plant species used to promote lactation were extracted from published or unpublished valuable reports of ethnobotanical surveys conducted in Niger for a comprehensive review. Six studies were reviewed. A total of thirteen (13) plant species belonging to 11 families were recorded as being used as galactagogues by Nigeriens. This review poined out three species including Sclerocarya birrea, Caralluma longidens and Guiera senegalensis to be the most cited. Using plants to promote lactation in breastfeeding mothers is a very common practice in Niger republic. However, there are no scientific reports based on laboratory studies which could justify the rational use of these plants. Further local studies are urgently needed to confirm the efficacy and safety of these plants.